Analysis of Zakat Literacy, Zakat Transparency, and Sharia Compliance OPZ Performance with Puskasbaznas Index - Abdul Sidik; Rossje V Suryaputri (Jurnal Syntax Transformation, 2023)
Zakat Management Organization is an organization that is authorized and obliged to implement the system and management of public funds. As a country with a Muslim population of 87%, the potential amount of zakat is very large, the latest measurement of zakat potential in Indonesia according to Puskas (2019) reached Rp 233.9 trillion. As the person in charge and management of public funds, of course, the management of the zakat management organization must have good performance in order to gain the trust of the muzaki. However, in its development, it turns out that there are still many people who lack trust in conducting zakat transactions in official government organizations. This study used quantitative data with secondary data from the Puskasbaznas index. The purpose of this study is to determine the performance of zakat managers. The results showed that there was a significant influence between zakat literacy and Sharia compliance on performance, while zakat transparency did not have a significant effect on performance. Meanwhile, simultaneously, zakat literacy, zakat transparency, and Sharia compliance have a significant effect on the performance of zakat managers.